Language variation among business abstracts. (2016) - Duncan, Benjamin
The old credo of business is to always put the needs and well-being of the customer first. But what the credo fails to mention is that business writing to an international audience and global consumer market today needs largely be done in one language - English. This project aims to examine linguistic variation among business abstracts according to the authors' countries of origin and first languages. The significance of these studies regards the growing number of second-language (L2) business managers and researchers attempting to publish and disseminate their research and business innovations to English-language journals, foreign markets and colleagues, but who find themselves locked out of the discussion due to unfamiliarity with the linguistic and discourse conventions. Through the use of the natural language processing tool, CohMetrix, the present examination aims to provide a more thorough and quantitative understanding of the prototypical linguistic components in business writing, and to suggest how word-, sentence-, and discourse-level structures can be isolated, taught, and developed as educational materials.